Comparison of Sexual Function between Nulliparous with Multiparous Pregnant Women - Kobra Abouzari Gazafroodi; Fatemeh Najafi; Ehsan Kazemnejad; Fatemeh Rahimikian; Mamak Shariat; Parvin Rahnama (Tehran University of Medical Sciences, 2012)
Background & Aim: Pregnancy can conflict with sexual function that can be affected by physical and psychological changes during pregnancy. The aim of this study was to compare sexual functions between nulliparous and multiparous pregnant women referred to health centers in Eastern district of Guilan. Methods & Materials: This cross-sectional study was carried out in Guilan during 2009-2010. We used convenient sampling method to select 554 pregnant women. Data were gathered using a questionnaire including demographic characteristics, sexual function and fear of harm to fetus. The SPSS-16 was used to analyze the data by the Mann-Whitney U and Generalized linear models. The level of significance was set at 5%. Results: There was no significant difference between nulliparous and multiparous pregnant women regarding sexual function in the first and second trimesters of pregnancy (P=0.353, P=0.251). There were significant differences between nulliparous and multiparous pregnant women regarding sexual desire (P=0.002), arousal (P=0.01), orgasm (P=0.01), pain (P=0.02) and sexual function total score (P=0.016). There was significant difference between nulliparous and multiparous pregnant women regarding sexual function (P=0.008). Conclusion: Sexual counseling and rehabilitation programs should be compiled as part of the comprehensive care of prenatal care especially for multiparous pregnant women.